Age‐related changes in molar topography and shearing crest length in a wild population of mountain Gorillas from Volcanoes National Park, Rwanda. Issue 1 (8th February 2016) - Glowacka, Halszka; McFarlin, Shannon C.; Catlett, Kierstin K.; Mudakikwa, Antoine; Bromage, Timothy G.; Cranfield, Michael R.; Stoinski, Tara S.; Schwartz, Gary T.
ABSTRACT: Objectives: Great ape teeth must remain functional over long lifespans. The molars of the most folivorous apes, the mountain gorillas, must maintain shearing function for 40+ years while the animals consume large quantities of mechanically challenging foods. While other folivorous primates experience dental senescence, which compromises their occlusal surfaces and affects their reproductive success as they age, it is unknown whether dental senescence also occurs in mountain gorillas. In this article, we quantified and evaluated how mountain gorilla molars change throughout their long lifespans. Materials and Methods: We collected high‐resolution replicas of M 1 s ( n  = 15), M 2 s ( n  = 13), and M 3 s ( n  = 11) from a cross‐sectional sample of wild mountain gorilla skeletons from the Virunga Volcanoes, ranging in age from 4 to 43 years. We employed dental topographic analyses to track how aspects of occlusal slope, angularity, relief index, and orientation patch count rotated change with age. In addition, we measured the relative length of shearing crests in two‐ and three‐dimensions. Results: Occlusal topography was found to decrease, while 2D relative shearing crest length increased, and 3D relative crest lengths were maintained with age. Discussion: Our findings indicate that shearing function is maintained throughout the long lifetimes of mountain gorillas. Unlike the dental senescence experienced by other folivorous primates, mountain gorillas do not appear to possess senesced molars despite their long lifetimes, mechanically challenging diets, and decreases in occlusal topography with age. Am J Phys Anthropol 160:3–15, 2016. © 2016 Wiley Periodicals, Inc.